Respuesta :
Answer:
[tex]t=\frac{1}{2}[/tex]
Step-by-step explanation:
We want to solve for the value of t in the equation
[tex]4(t+\frac{1}{4})=3[/tex]
Since we are trying to make t the subject of the formula (or isolate t)
Divide both sides by 4
[tex]\dfrac{4(t+\frac{1}{4})}{4} =\dfrac{3}{4}[/tex]
This gives us:
[tex]t+\frac{1}{4} =\frac{3}{4}[/tex]
Next, we subtract [tex]\dfrac{1}{4}[/tex] from both sides
[tex]t+\frac{1}{4}-\frac{1}{4} =\frac{3}{4}-\frac{1}{4}\\t=\dfrac{3-1}{4}=\frac{2}{4}=\frac{1}{2}\\t=\frac{1}{2}[/tex]